2017
DOI: 10.1074/jbc.m117.788729
|View full text |Cite
|
Sign up to set email alerts
|

The transmembrane domain of the p75 neurotrophin receptor stimulates phosphorylation of the TrkB tyrosine kinase receptor

Abstract: The function of protein products generated from intramembraneous cleavage by the γ-secretase complex is not well defined. The γ-secretase complex is responsible for the cleavage of several transmembrane proteins, most notably the amyloid precursor protein that results in Aβ, a transmembrane (TM) peptide. Another protein that undergoes very similar γ-secretase cleavage is the p75 neurotrophin receptor. However, the fate of the cleaved p75 TM domain is unknown. p75 neurotrophin receptor is highly expressed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Similarly, our study also showed these changes. Moreover, the transmembrane domain of the p75 stimulates phosphorylation of the TrkB during brain injury, Alzheimer's disease, and epilepsy (Saadipour et al, 2017). Elevated p75 protein/TrkB phosphorylation levels were also found in OT groups in our study, which likely indicated maladaptation.…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, our study also showed these changes. Moreover, the transmembrane domain of the p75 stimulates phosphorylation of the TrkB during brain injury, Alzheimer's disease, and epilepsy (Saadipour et al, 2017). Elevated p75 protein/TrkB phosphorylation levels were also found in OT groups in our study, which likely indicated maladaptation.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, amyloidogenesis is aggravated by the interaction of beta-site amyloid precursor protein cleaving enzyme-1 (BACE1) with p75 upon the binding of Aβ to p75 [ 21 ]. In contrast, it was shown that the p75ECD has a neuroprotective effect against Aβ toxicity [ 61 ] and that transmembrane domain of p75, has trophic effects by inducing phosphorylation of TrKB [ 62 ]. Our results emphasize the important contribution of p75 signaling, including p75ICD internalization and apoptosis, in AD pathogenesis upon AGE-modified proBDNF stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Hemolymph of 60-80 flies that were fed with standard fly food was collected as previously described 36 . The total protein in the hemolymph was measured by Bradford (Bio-Rad) and the concentration is adjusted to 1 mg/mL in PBS 44 . 10 μL of hemolymph was dropped on 0.2 μm nitrocellulose membrane (GE Healthcare, Uppsala, CA, USA) and left at room temperature until to be dried.…”
Section: Dot Blot Assaymentioning
confidence: 99%